Trends of blood pressure, raised blood pressure, hypertension and its control among Italian adults: CUORE Project cross-sectional health examination surveys 1998/2008/2018 - Graziano Onder; Luigi Palmieri; Michele Massimo Gulizia; Chiara Donfrancesco; Anna Di Lonardo; Cinzia Lo Noce; Brigitta Buttari; Elisabetta Profumo; Francesca Vespasiano; Serena Vannucchi; Ferruccio Galletti; Daniela Galeone; et al. (BMJ Open, 2022)
Objectives To assess in the Italian general adult population the trends of blood pressure (BP) and prevalence of raised BP (RBP), hypertension and its control in order to evaluate population health and care, and the achievement of an RBP 25% relative reduction as recommended by the WHO at population level.Design Results comparison of health examination surveys, cross-sectional observational studies based on health examination of randomly selected age and sex stratified samples including residents aged 35–74 years. Data of the 2018/2019 survey were compared with the previous ones collected in 1998/2002 and 2008/2012.Setting Health examination surveys conducted in Italy within the CUORE Project following standardised methodologies.Participants 2985 men and 2955 women examined in 1998/2002, 2218 men and 2204 women examined in 2008/2012 and 1031 men and 1066 women examined in 2018/2019.Primary and secondary outcome measures Age-standardised mean of BP, prevalence of RBP (systolic BP and/or diastolic BP ≥140/90 mm Hg), hypertension (presenting or being treated for RBP) and its awareness and control, according to sex, age class and educational level.Results In 2018/2019, a significant reduction was observed in systolic BP and diastolic BP in men (1998/2002: 136/86 mm Hg; 2008/2012: 132/84 mm Hg; and 2018/2019: 132/78 mm Hg) and women (132/82 mm Hg, 126/78 mm Hg and 122/73 mm Hg), and in the prevalence of RBP (50%, 40% and 30% in men and 39%, 25% and 16% in women) and of hypertension (54%, 49% and 44% in men and 45%, 35% and 32% in women). Trends were consistent by age and education attainment. In 2018/2019, hypertensive men and women with controlled BP were only 27% and 41%, but a significant favourable trend was observed.Conclusions Data from 2018/2019 underlined that RBP is still commonly observed in the Italian population aged 35–74 years, however, the WHO RBP target at that time may be considered met.